2010
DOI: 10.1007/s11999-009-1089-y
|View full text |Cite
|
Sign up to set email alerts
|

Reintervention after Mobile-bearing Oxford Unicompartmental Knee Arthroplasty

Abstract: BackgroundMedial compartment osteoarthritis is a common disorder that often is treated by unicompartmental knee arthroplasty (UKA). Although the Oxford 3 prosthesis is commonly used based on revision rate and cumulative survival, our experience suggests that although there may be adequate implant survival rates, we observed a worrisome and undisclosed reintervention rate of nonrevision procedures. Purpose We describe the frequency and cause of repeat intervention subsequent to implanting this device. Methods B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Higher early minor reintervention rates for the mobile-bearing UKA were reported [7,8,11,41]. Comparative studies did not find any differences in terms of survivorship; however, the followup was limited [7,8,11,25,41]. Our goal was therefore to compare the long-term function and survivorship of fixedand mobile-bearing UKA.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Higher early minor reintervention rates for the mobile-bearing UKA were reported [7,8,11,41]. Comparative studies did not find any differences in terms of survivorship; however, the followup was limited [7,8,11,25,41]. Our goal was therefore to compare the long-term function and survivorship of fixedand mobile-bearing UKA.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies comparing the reintervention rate [8] and the short-and midterm survivorship [9,11,41] after fixed-or mobilebearing UKA suggested a higher early minor reintervention rate for the mobile-bearing UKA [8]. However, whether the long-term function and survivorship are similar is unclear.…”
Section: Introductionmentioning
confidence: 98%
“…8,10,11,16 The bearing dislocation is caused by posterior impingement, ligament laxity, decreased posterior slope, and varus deformity. 6,9,17,18 Meniscal bearing dislocation has been reported in anterior, posterior, and lateral bearing locations. [10][11][12][13] In the anterior and posterior dislocation cases, since meniscal bearing can completely dislocate from the joint space, the main clinical symptoms are sudden locking, limitation of motion, acute knee pain, and swelling.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] But it has the potential risk of dislocation of meniscal bearing. [6][7][8][9] Symptoms caused by most meniscal bearing dislocations include acute pain, knee swelling, locking, and radiographs which can confirm the anterior, posterior, or lateral dislocation of the bearing. [10][11][12][13] However, in rare cases, it has been reported that radiologic diagnosis was delayed and confirmed late if symptoms were mild even though the liner had dislocated.…”
Section: Introductionmentioning
confidence: 99%
“…19,20,22 Also, UKA has been cited to cause an increased rate of certain complications including femoral condyle fracture, tibial plateau fracture, free cement fragments, insert dislocation, and stiffness. [23][24][25][26] These findings have resulted in preference of TKA over UKA in some surgeons. 7 However, our results confirmed that UKA is a safe and effective procedure.…”
Section: Discussionmentioning
confidence: 99%